1993
DOI: 10.1111/j.1365-2621.1993.tb04285.x
|View full text |Cite
|
Sign up to set email alerts
|

Gelatinization and Retrogradation Characteristics of Hydroxypropylated and Cross‐linked Rices

Abstract: Chemically modified rices were prepared by treating with propylene oxide and epichlorohydrin. Gelatinization and retrogradation characteristics of these modified rices were investigated by using DSC and amylograph. Hydroxypropylation of rice caused an extreme decrease in gelatinization temperature from 62°C to 50°C and reduced the retrogradation rate of cooked rice. In rice treated by both hydroxypropylation and cross-linking the retrogradation was reduced more than for hydroxypropylated rice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(25 citation statements)
references
References 7 publications
2
22
0
1
Order By: Relevance
“…acetylated (Hoover & Sosuskl 1985) and hydroxypropylated (Hoover et al. 1988;Yook et al 1993) groupS Into starch chains has been shown to influence starch retrogradation by retarding amylose and amylopectin chain aggregation during storage. Hoover et al (1988) reported that hydroxypropylated field pea starch showed less retrogradation dunng frozen storage compared to the unmodified starch Takahashi et al (1989) studied the gel properties of wheat and corn starches cross linked after acetylation and hydroxypropylation.…”
Section: 5248physicalmodiflcationmentioning
confidence: 99%
“…acetylated (Hoover & Sosuskl 1985) and hydroxypropylated (Hoover et al. 1988;Yook et al 1993) groupS Into starch chains has been shown to influence starch retrogradation by retarding amylose and amylopectin chain aggregation during storage. Hoover et al (1988) reported that hydroxypropylated field pea starch showed less retrogradation dunng frozen storage compared to the unmodified starch Takahashi et al (1989) studied the gel properties of wheat and corn starches cross linked after acetylation and hydroxypropylation.…”
Section: 5248physicalmodiflcationmentioning
confidence: 99%
“…Yeh and Yeh (1993) also reported that cross-linking increased the heat of gelatinization for rice starch. However, according to Yook et al (1993), the cross-linked rice starch exhibited a lower value of heat of gelatinization than native rice starch because cross-linking reduced the portion of starch granules that could be gelatinized. In this study, the T o, T p and ∆H gel of cross-linked starches from rice, maize and potato were higher than those of their native counterpart starches at the same reaction conditions of 0.3% EPI.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…Retrogradation is influenced by starch structure (Russell, 1987;Orford eta!., 1987), storage temperature (Jankowski and Rha, 1986), moisture content (Longton and LeGrys, 1981;Zeleznak and Hoseney, 1986), lipids (Eliasson and Ljunger, 1988;Huang and White, 1993), sugars (Kohyama and Nishinari, 1991;Wang and Jane, 1994), salts (Ciacco and Fernandes, 1979;Bello-Perez and ParedesLopez, 1995), and physical and chemical modifications (Orford et al, 1993;Gunaratne and Hoover, 2002;Yook et al, 1993 (Janecek 2000). It consists of twenty seven different enzyme specificities (Horvathova et al, 2000).…”
Section: Retrogradationmentioning
confidence: 99%